2012
DOI: 10.1148/rg.325115126
|View full text |Cite
|
Sign up to set email alerts
|

From the Radiologic Pathology Archives: Cardiac Lymphoma: Radiologic-Pathologic Correlation

Abstract: Lymphoma of the heart and pericardium is usually present as one aspect of disseminated disease and rarely occurs as a primary malignancy. It accounts for 1.3% of primary cardiac tumors and 0.5% of extranodal lymphomas. Cardiac lymphomas are most commonly diffuse large cell lymphomas and frequently manifest as an ill-defined, infiltrative mass. Atrial location is typical; the right atrium is most often affected. Pericardial thickening or effusion is often a common early feature of disease. Infiltration of atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
72
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 42 publications
1
72
0
2
Order By: Relevance
“…Cardiac involvement due to metastasis of malignant tumors is relatively uncommon and is associated with poor prognosis. Autopsy studies have shown up to 10% -12% of cardiac involvement in all patients with malignancy [1]. The most frequent metastatic malignancies, in absolute terms, to the heart are lung and breast carcinomas, followed by lymphomas [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac involvement due to metastasis of malignant tumors is relatively uncommon and is associated with poor prognosis. Autopsy studies have shown up to 10% -12% of cardiac involvement in all patients with malignancy [1]. The most frequent metastatic malignancies, in absolute terms, to the heart are lung and breast carcinomas, followed by lymphomas [2].…”
Section: Introductionmentioning
confidence: 99%
“…Primary cardiac lymphoma rarely occurs and accounts for 1.3% of primary cardiac tumors and 0.5% of extranodal lymphomas, the right atrium is most common location, and diffuse large B-cell lymphomas (DLBCL) is usual form [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the diagnosis is often difficult, early diagnosis and treatment is a key to success for good outcome [1].…”
Section: Discussionmentioning
confidence: 99%
“…It usually affects the right heart chamber [2,4]. Dyspnea is the most common symptom, followed by chest pain and constitutional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, it is isointense on T1 weighted, iso-to hyperintense on T2 weighted, and is not suppressed on fat suppression sequences. PCL demonstrates heterogeneous enhancement following gadolinium administration [3,4]. Encasement of the RCA, when present, favors PCL over angiosarcoma [5].…”
Section: Discussionmentioning
confidence: 99%